Integrated Information Technology Descriptive Text Comprehension Reading Skills (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe and analyze the implementation of information technology integration in learning descriptive text reading skills in the 7th grade of SMP Nahdlatul Wathan Mataram. This study uses a case study approach with descriptive qualitative methods. In-depth observations were conducted in two stages during the Indonesian language learning process that integrated information technology, focusing on descriptive text reading skills. The research location is SMP Nahdlatul Wathan Mataram, Jalan Kaktus No. 1-3 Gomong, Mataram. The subjects of the study are 21 students from the 7th grade of SMP Nahdlatul Wathan Mataram. Data collection techniques include participatory observation, in-depth interviews with teachers and students, as well as documentation. The research results show that the integration of information technology in learning, particularly the use of projectors and Chromebooks to access e-book applications, has a significant impact and increases the efficiency and effectiveness of the learning process for reading descriptive texts. The use of this technology stimulates active student participation and expands their understanding of the descriptive texts being studied. Students show high enthusiasm in interacting with technology-based learning media. However, there are several identified obstacles, including limited internet access in some school areas and the lack of participation and motivation from some students during group discussion stages.